The influence of purchase date and flight duration over the dispersion of airline ticket prices - Tomasz Stanisław Szopiński; Robert Nowacki (Contemporary Economics, 2015)
For many years, the air travel market has been the most regulated sector of the economy. Within the last few decades, it has undergone profound change, which is largely a consequence of changes in the law. Another factor that exerted influence on the market was the popularization of new information and communication technologies that affected the interaction between service providers and clients. Due to the application of modern technologies, it is easier for tradesmen to implement pricing policies to maximize profits or minimize losses. In turn, customers acquired a tool for comparing prices, which aids them in selecting the most advantageous offer from their point of view. This study aims to provide an answer to the following questions: how does flight duration affect the price dispersion of airline tickets and does price dispersion increase as the date of departure approaches. To answer these questions, airline ticket prices for flights on the route: Warsaw-London-Warsaw and the route: Warsaw-New York-Warsaw were observed between August 14 and November 14, 2014. Price dispersion increased on both routes as the date of departure approached. Analysis of price variation over time has revealed that longer flights (WAW-ZYP-WAW vs WAW-LHR-WAW) were less dispersed in terms of prices in the period under analysis.
Keywords: D12; F12; L81; 330; airline ticket dispersion; air transport market; price comparison; pricing policy